Akuntansi Persediaan Barang Atau Perlengkapan Berdasarkan PSAP Nomor 05 Pada Kantor Kepolisian Resor Bolaang Mongondow Selatan - Lumenta, Christy Patricia; Morasa, Jenny; Pinatik, Sherly (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2021)
Inventories are current assets in the form of goods or equipment to support operational activities in government agencies. A good inventory recording system and in accordance with applicable accounting principles can improve the performance of services provided by government agencies. This study aims to determine the suitability of Accounting for goods or equipment based on Government Accounting Standards Statement (PSAP) Number 05, which is applied to the South Bolaang Mongondow Police Office. Data collection techniques used are interviews and observations. The results showed that the inventory accounting in the southern Bolmong Police was mostly in accordance with the Statement of Government Accounting Standards (PSAP) No. 05.